Policy Model of Zoning System in the Admission of New Students and Their Prospects in Indonesia - Muhartono, Djoko Siswanto (CV. Tripe Konsultan, 2024)
This research aims to construct a policy model for new student admissions, abbreviated as PPDB, with a zoning system and its prospects. The research approach uses a qualitative approach with data sources from State Junior High School 1 or abbreviated as SMPN 1 Gampengrejo and State Junior High School 3 or abbreviated as SMPN 3 Plosoklaten, Kediri County. There were ten key informants involved in this study. The analysis method is a comparative method for constructing a model of a public administration system. The findings of the study are: (1) every admission of new students in the education unit is regulated by the ministry of primary and secondary education; (2) there are technical instructions from the district/city government; (3) there is a decree of the head of the education unit regarding the executive committee; (4) provision of complete data on prospective students in zoning in accordance with the provisions of the central government; (5) coordination between school principals and between school committees to ensure that prospective students get schools; (6) the head of the education unit supports the executive committee; (7) suppressing obstacles that interfere with the smooth implementation of the zoning system; (8) developing an effective public information system, through feedback to provide input to the PPBD implementation system; (9) the transformation from PPDB to the New Student Admission System (SPMB) at the philosophical level is relatively unchanged; and (10) the change of the student admission system, the important thing is that all children of school age, all are obliged to get a school with the principle of